Optimalisasi Biaya Distribusi dari Pabrik Bluder Koe ke Berbagai Cabang Bluder Koe dengan Metode Transportasi - Intan Lailatul Mahmudah; Selvi Rahmadany; Gracia Putri Maharani; Yuvi Safitri; Titis Purwaningrum (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
The optimization of distribution costs from the Koe Bluder factory to various branches is the problem in this study, which aims to minimize total delivery costs and maintain service quality and time efficiency. In the context of the food industry, especially the increasingly popular bluder cake, effective distribution management is crucial to meet customer demand without increasing operational costs. This study uses transportation methods to analyze and optimize the distribution process, which includes determining the initial allocation and identifying factors that affect transportation costs. The approaches used include the North West Corner (NWC) and Modified Distribution Method (MODI) methods to allocate and minimize shipping costs. The analysis results show that a total transportation cost of Rp 124.825,000 can be achieved using both methods. This research highlights the importance of efficient distribution planning in improving operational efficiency and customer satisfaction, with an emphasis on reducing costs without sacrificing service quality